PERSEPSI MAHASISWA KEPERAWATAN TENTANG PEMBELAJARAN SIMULASI PENANGGULANGAN BENCANA PADA MATA KULIAH KEPERAWATAN GAWATDARURAT - Hendriyeni, Pradhita (Akper Kesdam I/Bukit Barisan Padang, 2024)
Nurses are the health profession with the largest number compared to other health professions. One of the competencies that nurses must have is to play a role in disaster management. This competency is obtained in the learning process at universities. Theoretical implementation into nursing practice is one of the challenges in the learning process in emergency. Simulation is one of the learning models that can be used to integrate nursing theory with practical skills in the educational process. This study aims to evaluate students' perceptions regarding the implementation of disaster management simulation learning in the Emergency Nursing and Disaster Management course at the DIII Nursing Study Program, Akper Kesdam I Bukit Barisan Padang. The research respondents were students who were taking Emergency Nursing and Disaster Management learning. Data collection was carried out through a questionnaire with a Likert scale containing questions about students' perceptions of various aspects of the simulation implementation. The results of this study indicate that in general, students' perceptions of the implementation of disaster management simulations in the Nursing Disaster course are very positive